Analisis Perkembangan Perbankan Syariah Di Indonesia Dengan Melaksanakan Spin Off Pada Unit Usaha Syariah - Ely Eka Saputri; Siti Elita; Anisatul Kamilah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
There was a spin off policy initially envisaged in Act No. 12 of 2008, but by mid-2023, the OJK subsequently issued POJK No.12 of 2023. The study aims to analyze the development of Sharia banking in Indonesia by implementing a spin-off on the Sharia Business Unit owned by a conventional general bank. This type of research is qualitative research, with the type of analysis used namely analysis of skunder data presented descriptively. This research is carried out by means of a library study or literature review which is taken from various available sources such as data or documents published by the Bank of Indonesia, journals, books, articles, as well as other reading findings related to the research topic. The results of this study show that the development of Sharia banking in Indonesia by implementing a spin-off on the Sharia Business Unit owned by the Conventional General Bank has grown significantly, it is proven with several banks that have joined BUS, recorded in the performance report of the OJK that 14 banks have become Sharia General Bank using different schemes in the process.